Effectiveness of Cooperative Learning Strategy among Secondary Level Students in Nepal - Acharya, Milan (Innovative Research Journal, 2025)
This study aimed to evaluate the effectiveness of cooperative learning strategies in improving the academic performance, motivation, and retention of secondary-level students in health and population education. An experimental research design was employed, involving pre-test and post-test assessments of two equivalent groups of grade ten students from two schools in Kirtipur. The experimental group was taught using cooperative learning methods, while the control group followed traditional teaching approaches. Data were collected using a validated 30-item multiple-choice achievement test. Statistical analyses, including mean scores, standard deviations, variances, and t-tests, indicated a significant improvement in post-test scores for the experimental group compared to the control group. These findings confirm the effectiveness of cooperative learning in fostering active engagement and critical thinking among students. It is recommended that cooperative learning strategies be integrated into teaching practices to enhance student participation and academic achievement in Nepalese schools.